Mechanical and Self-Healing Performances of Crumb Rubber Modified High-Strength Engineered Cementitious Composites - Jiangtao, Yu; Fangming, Jiang; Qiong, Xing; Qi, Yang; Mi, Li (Frontiers in Materials, 2021)
High-strength engineered cementitious composite (HS-ECC) reinforced with polyethylene (PE) fiber characterizes wider crack widths than the conventional polyvinyl alcohol fiber-reinforced ECC (PVA-ECC), weakening the self-healing potential of HS-ECC. The properties of HS-ECC are tailored by introducing crumb rubber (CR), as artificial flaws can lower the matrix toughness and the crack width, leading to an enhanced self-healing potential of HS-ECC. In this study, CR is used to entirely replace silica sand (SS) with three equivalent aggregate-to-binder ratios of 0.2, 0.4, and 0.6, and two CR particle sizes (i.e., CR1 and CR2) are also considered to investigate the effects on density, compressive properties, and tensile performances of HS-ECC. Although CR substitution of SS influences adversely the mechanical strengths of HS-ECC, it can reduce the HS-ECC matrix fracture toughness, activate more microcracks, and reduce the crack width. Moreover, CR-modified HS-ECC specimens featuring the smallest crack width were preloaded to three specific strain levels, including 0.5%, 1.0%, and 2.0%, and then experienced wet–dry conditioning to exhibit effective mechanical and non-mechanical property recovery. The further hydration of binder materials enhances the interfacial bond stress and thus retains the mechanical performances of self-healed HS-ECC, which is expected to improve the practical application and benefit the sustainability of HS-ECC.